ACE (Angiotensin-Converting Enzyme) Inhibition Reverses Vasoconstriction and Impaired Dilation of Pial Collaterals in Chronic Hypertension. Issue 1 (July 2020) - Li, Zhaojin; Lindner, Devon P.; Bishop, Nicole M.; Cipolla, Marilyn J.
Abstract : Leptomeningeal anastomoses (LMAs) are pial collaterals that perfuse the penumbra and important for stroke outcome. We previously showed LMAs from SHRs (spontaneously hypertensive rats) were vasoconstricted compared with normotensive Wistar rats. Here, we investigated mechanisms by which hypertension causes LMA vasoconstriction. SHRs were treated with the ACE (angiotensin-converting enzyme) inhibitor captopril, an Ang II (angiotensin II)–independent antihypertensive agent hydralazine, or vehicle for 5 weeks in drinking water (n=8/group). A group of Wistar rats (n=8) had regular drinking water served as controls. Blood pressure was measured twice weekly by tail-cuff. LMAs were isolated and studied under pressurized conditions. Vasoreactivity of LMAs, including myogenic responses, reactivity to Rho-kinase inhibitor Y-27632, and nitric oxide were measured. Both captopril and hydralazine lowered blood pressure in SHRs similar to Wistar. However, only captopril normalized LMA increased tone compared with untreated SHRs (15±2% versus 50±3%; P <0.01) that was similar to Wistar (16±2%) but not hydralazine (38±6%; P >0.05). Vasodilatory response of LMAs to Y-27632 was impaired in SHRs compared with Wistar (28±3% versus 81±4%; P <0.01) that was restored by captopril (84±5%; P <0.01) and partially hydralazine (59±4%). LMAs from all groups constricted similarly to NOS (NO synthase) inhibition; however, the vasodilatory response of LMAs to the nitric oxide donor sodium nitroprusside was impaired in SHRs compared with Wistar rats (29±4% versus 80±2%; P <0.01) that was restored by captopril (84±4%; P <0.01), not hydralazine (38±8%; P >0.05). These results suggest that ACE inhibition during chronic hypertension reversed vascular dysfunction and hyperconstriction of LMAs that could improve stroke outcome by increasing collateral perfusion. Abstract : Supplemental Digital Content is available in the text.